A physiological Explanation of Drought Effect on Flag-Leaf Specific Weight and Chlorophyll Content of Barley - Mahmood, Yadgar Ali; Mohammed, Masood Saber; Hassan, Halgurd Nasraden (Iraqi Journal of Science, 2019)
This study was carried out in Kalar technical institute, Sulaimani Polytechnic University in Garmian region, Iraq during 2016-17 and 2017-18 seasons. Five hybrid genotypes of barley were tested under drought and irrigated conditions to detect the flag-leaf specific weight, chlorophyll content index (SPAD; The Soil Plant Analysis Development chlorophyll meter) and the period from anthesis to physiological maturity. Across both years 2016-17 and 2017-18, there was no effect of drought on flag-leaf specific weight, however, SPAD was reduced by 4.77 and the period between anthesis and maturity was shortened by almost two days. Genotype 3//14 scored the highest values of flag-leaf specific weight (7.765 mg cm-2)and SPAD (25.56), and stayed green for the longest period (28.69 days) (P=0.05), showing its ability to be more tolerant to moisture reductionas compared to the other tested genotypes. In order to explain the physiological mechanisms among the assessed traits under both irrigated and drought conditions, linear regression analysis was applied for both seasons and averaged over seasons. A positive linear relationship was shownbetween flag-leaf specific weight and SPAD under both irrigated (R2=0.83; P=0.03) and drought (R2=0.76; P=0.05) conditions, explaining the high flag-leaf chlorophyll content resulting from high specific weight of leaves. The high flag-leaf specific weight was also associated with longer periods for leaves to stay-green after anthesis, under both irrigated (R2=0.91; P=0.01) and drought (R2=0.79; P=0.04) conditions, which provides a great chance to accumulate more resources of carbohydrates and protein in the grain and, consequently,a higher throughput of yield.